The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1111/jen.12921
|View full text |Cite
|
Sign up to set email alerts
|

Genetic structure of Cydiapomonella populations in Argentina and Chile implies isolating barriers exist between populations

Abstract: The codling moth (Cydia pomonella (L.)) is an invasive pest of pome fruits introduced to the Americas in the 19-20 th centuries. This pest is widespread on both sides of the Andes range separating Argentina and Chile. We performed an analysis of the population genetic variability and structure of C. pomonella in Argentina and Chile using 13 microsatellite markers and sampled C. pomonella from apple as the main host plant along its distribution area (approx. 1,800 km). A total of 22 locations (11 from Chile and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…The codling moth (Cydia pomonella (Linnaeus, 1758)) (Lepidoptera: Tortricidae) is among the most important and well-studied insects. Its genetics [1][2][3][4][5][6][7], resistance to chemical insecticides [8][9][10][11][12][13], monitoring and control strategies [14][15][16][17][18], effects of climate change on its biology and ecology [2,19], and many other phenomena have been studied in detail. It is the most harmful and widespread pest in apple orchards.…”
Section: Introductionmentioning
confidence: 99%
“…The codling moth (Cydia pomonella (Linnaeus, 1758)) (Lepidoptera: Tortricidae) is among the most important and well-studied insects. Its genetics [1][2][3][4][5][6][7], resistance to chemical insecticides [8][9][10][11][12][13], monitoring and control strategies [14][15][16][17][18], effects of climate change on its biology and ecology [2,19], and many other phenomena have been studied in detail. It is the most harmful and widespread pest in apple orchards.…”
Section: Introductionmentioning
confidence: 99%
“…Kuyulu and Genç [44] found low genetic differentiation among nine CM populations in Turkey, and Basoalto et al [45] found low genetic differentiation among 34 populations (F ST = 0.03) in Chile. Cichón et al [46] used 13 microsatellite markers for 22 locations in Chile and Argentina and found significant genetic differentiation among populations (FST = 0.085). Analyzing the geometric characteristics of the morphology (geometric morphometric tools) is a demonstrated monitoring tool for studying inter and intraspecific variation and is a useful tool to show forewing shape and size differences among codling moth populations [47].…”
Section: Introductionmentioning
confidence: 99%